UPAYA MENINGKATKAN KAPASITAS, KOMPETENSI, DAN DAYA SAING PELAKU UMKM RUMAH BUMN KOTA BANDUNG - Harianto Simarmata; Elan Rusnendar; Aninditha Putri Kusumawardhani; Theresia Manalu; Anang Bambang Pujianto; Ade Sintia Hendriani; Tomson Tomson (Universitas Mataram, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in supporting Indonesia’s economic development.. However, many MSME actors still face challenges in reaching wider markets due to limited human resource capacity, low digital literacy, and the continued use of traditional marketing strategies. These conditions result in limited market access and low business competitiveness. Therefore, targeted empowerment programs are needed to strengthen the capacity of MSME actors. This community service program aims to enhance the capacity, competence, and competitiveness of MSME actors at Rumah BUMN Bandung City so that they can better adapt to digital technological developments and changing market dynamics. The program was implemented through training seminars and interactive discussions involving 30 participants. The training focused on digital marketing, human resource capacity development, and strategic business planning. The results indicate significant improvements in participants’ competencies. Participants’ understanding of digital marketing increased from 50% to 85%, the use of social media for promotion increased from 45% to 80%, and understanding of business planning improved from 55% to 82%. In addition, product branding skills increased from 48% to 83%, while motivation and self-confidence rose from 60% to 90%. Participants also began utilizing social media and online marketplaces to support their business activities. Overall, the program positively contributed to improving participants’ capacity and competitiveness, enabling them to become more adaptive and competitive in the digital business environment.